The effect of consumer price index, export volume and exchange rate movement towards a commodity price changes: the case of dried cocoa beans / Nur Syuhadah Mohd Nor Rizan (Faculty of Business and Management, 2007)
One of the development strategies utilized by the agriculture sector is to encourage crop diversification with the aim to increase national income. Cocoa cultivation has a good potential to be an industrial crop which can be further developed. Considering cocoa cultivation is the third important crop after rubber and oil palm, it is pertinent that a dried cocoa price determinant study be conducted. Several studies show that the economic factors may give impact to the price of dried cocoa beans in Malaysia. This study will assess the extent to which the economic factors may affect the price of dried cocoa price. The objective or purpose of the study is to identify the impact of economic factors to the dried cocoa price. To analyze the effects of economic factors towards the dried cocoa price changes, this study consists of three independent variables which are Food Consumer Price Index (FCPI), export volume of cocoa beans and exchange rate using UK Pound Sterling while the dependent variable is the price of dried cocoa beans. The study consists of 7 years observations using the monthly basis from year 1999 until 2005. The sample data are 80 observations of all sets of variables. The statistical tool that will be use in the study is Multiple Linear Regression. This study will take necessary effort to identify what will happen to the price of dried cocoa beans according to the economic factors. This method will find the relationship of independent variables and dependent variable. The statistical test conducted by Statistical Package for Social Science (SPSS) to examine the significant.